Heritages in progress. Designing their regeneration - Françoise Blanc (Agathón)
To design with Heritage for the future within the complexity of its scales and its contemporary stakes opens an innovating field. The idea of ‘regeneration’ becomes a drive for project at all scales. The examination of this notion allows the introduction to the discourse, which is developed afterwards with the exposure of two meaningful experiments: they propose the current and future regeneration of Heritage within its large space context and open a new conceptual frame for the project. The case of Mont Saint Michel in France, a realized pilot project and the internationally collaborated academic works on the water supplies Heritage and the metropolitan sprawl in the territory of Jaipur-Amber, Rajasthan, illustrate the contribution to a founding reflection on the becoming of Heritages, seen as a renewable resource and innovative carrier.